A comparison of process modelling methods for healthcare redesign. (1st January 2013) - Mould, Gillian; Bowers, John
Two process modelling methods (pathway mapping and simulation), commonly used in healthcare redesign are compared. A framework for assessing modelling capability is developed with the aid of the literature. This framework is then used to compare the hard and soft modelling capabilities of the modelling methods in two healthcare redesign case studies. The first case study is the redesign of an emergency department and the second case study concerns orthopaedic outpatient clinics. It is found that pathway mapping is the most appropriate tool for the redesign of complex healthcare systems as in the case of the emergency department, where it is accessible to a wide range of users and promotes the understanding of the whole system. However for simpler, well-defined systems such as an outpatient clinic, simulation offers the further capability of predictive assessment which is valuable for a full quantitative evaluation of alternative redesign options.